Capacity Building of Post Graduate Alumni: Concrete Implications of Participatory Action Research Methods : - - Hadi, Samsul; Retnawati, Heri; Muhson, Ali; Prihono, Eko Wahyunanto; Lapele, Fitria; Kartianom, Kartianom; Negara, Habib Ratu Perwira (TAAWUN, 2026)
Alumni play a strategic role in strengthening academic networks and research dissemination. However, limited mastery of advanced data analysis remains a major barrier to publication in reputable international journals. This community service program aimed to enhance alumni data analysis capacity through a non-formal continuing education model integrating Participatory Action Research (PAR), Kirkpatrick’s evaluation framework, and hands-on training using R software. The program involved 38 graduate school alumni and was evaluated using the four Kirkpatrick levels. Results show that 68.42% of participants demonstrated high engagement (reaction), while 81.58% perceived strong relevance between training materials and their professional needs. Quantitative evaluation using PLS-SEM indicates that learning significantly influenced behavioral change (R² = 0.217), and behavior had a strong effect on results (R² = 0.399), reflected in increased frequency of R usage, application of advanced analytical techniques, and research collaboration. This program makes a real contribution in providing a structured, measurable, and sustainable model for strengthening alumni capacity, and can be replicated by other universities to improve the quality of publications and the productivity of data-based research.